Accuracy Analysis of a Robot System for Closed Diaphyseal Fracture Reduction. (17th October 2014) - Li, Changsheng; Wang, Tianmiao; Hu, Lei; Zhang, Lihai; Du, Hailong; Wang, Lifeng; Luan, Sheng; Tang, Peifu
We have developed a robot system for closed diaphyseal fracture reduction. Because accuracy is essential for the treatment effects of the robot system and for the safety of both the patients and surgeons, we analysed accuracy in a systematic way. Both the structure of the robot and the operation procedure are described. Using the transfer model of errors in series and the error differential solving method for parallel mechanisms, an error model was established, and the main influencing factors of errors were considered. The Monte Carlo method was used to perform the simulation based on the error model. Experiments of image registration, of the mechanism and of the whole robot system were tested in different aspects to verify that the results of the simulation are correct. The system accuracy was compared with clinical standards to show that the robot system fulfilled the requirements for closed diaphyseal fracture reduction. The accuracy analysis method also provides an efficient path for other medical robots.